H‐Bonded Counterion‐Directed Catalysis: Enantioselective Gold(I)‐Catalyzed Addition to 2‐Alkynyl Enones as a Case Study. Issue 38 (13th July 2022) - Martí, Àlex; Montesinos‐Magraner, Marc; Echavarren, Antonio M.; Franchino, Allegra
Abstract: H‐bonded counterion‐directed catalysis (HCDC) is a strategy wherein a chiral anion that is hydrogen‐bonded to the achiral ligand of a metal complex is responsible for enantioinduction. In this article we present the application of H‐bonded counterion‐directed catalysis to the Au(I)‐catalyzed enantioselective tandem cycloisomerization‐addition reaction of 2‐alkynyl enones. Following the addition of C‐, N‐ or O‐centered nucleophiles, bicyclic furans were obtained in moderate to excellent yield and enantioselectivity (28 examples, 59–96 % yield, 62 : 38 to 95 : 5 er). The optimal catalytic system, comprising a phosphinosquaramide Au(I) chloride complex and a BINOL‐derived phosphoramidate Ag(I) salt, was selected in a combinatorial fashion from a larger library with the help of high‐throughput screening. An enantioselectivity switch of ca. 120 Δee% was observed upon addition of the achiral Au(I) component to the Ag(I) salt. Abstract : H‐bonded counterion‐directed catalysis has been applied to the enantioselective tandem cycloisomerization‐addition to 2‐alkynyl enones. The addition of C‐, N‐ or O‐centered nucleophiles catalyzed by a phosphinosquaramide Au(I) chloride/chiral Ag(I) phosphoramidate system afforded bicyclic furans in moderate to excellent yield and enantioselectivity (28 examples, 59–96 % yield, 62 : 38 to 95 : 5 er).